Promoting the transfer and use of environmentally sound technologies : a review of policies (UN New YorkUS, 1997)
Reviews selected policy options, policy options that have emerged specifically in relation to the protection of the environment as well as more traditional policy instruments which have both a direct and indirect bearing on environmental objectives.
DC